IMPLEMENTATION OF STUNTING PREVENTION POLICY IN BANYUMAS REGENCY - Saputra, Anggara Setya; Suryoto, Suryoto (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
Abstract-This study discusses the implementation of policies in an effort to overcome stunting problems in the Banyumas Regency area. The issue of stunting has become a major point of concern for the government that must be resolved starting from the village, regional and central government levels. Banyumas Regency is one of the regions that has a high tendency to commitment in efforts to tackle and reduce stunting that is happening now. This study aims to explain how the policy implementation process is carried out in the hope of being able to overcome and reduce stunting rates in Banyumas Regency. This study also looks at how the government is in carrying out its roles and responsibilities in controlling and accelerating the reduction of stunting in the community. This research method uses descriptive qualitative methods with data analysis techniques using data triangulation techniques and the source of this research informants is focused on the ability according to the data by using sampling purposes. The results of this study look at the aspects of idealized policy where, stunting prevention efforts in Banyumas Regency are in accordance with the rules and procedures contained in regional regulations and the regent’s decree. Target group in this policy is the community that is the target of the stunting prevention program. Implementing organization, namely the implementing group, both from the government, which are members of the relevant agencies, Integrated Healthcare Center community groups, and the private sector, namely the rotary club. Environmental factors faced in the implementation of stunting prevention policies are related to social and economic factors of the community. The condition of malnutrition that causes stunting is also inseparable from the socio-economic conditions of the people with low incomes. AbstraksiPenelitian ini membahas tentang implementasi kebijakan dalam upaya mengatasi masalah stunting di wilayah Kabupaten Banyumas. Masalah stunting telah menjadi titik perhatian utama bagi pemerintah yang harus diselesaikan mulai dari tingkat desa, pemerintah daerah dan pemerintah pusat. Kabupaten Banyumas merupakan salah satu daerah yang memiliki kecenderungan komitmen yang tinggi dalam upaya penanggulangan dan pengurangan stunting yang terjadi saat ini. Penelitian ini bertujuan untuk menjelaskan bagaimana proses implementasi kebijakan yang dilakukan dengan harapan dapat mengatasi dan menurunkan angka stunting di Kabupaten Banyumas. Kajian ini juga melihat bagaimana pemerintah dalam menjalankan peran dan tanggung jawabnya dalam mengendalikan dan mempercepat penurunan stunting di masyarakat. Metode penelitian ini menggunakan metode deskriptif kualitatif dengan teknik analisis data menggunakan teknik triangulasi data dan sumber informan penelitian ini difokuskan pada kemampuan menurut data dengan menggunakan tujuan sampling. Hasil penelitian ini melihat aspek kebijakan yang diidealkan dimana upaya pencegahan stunting di Kabupaten Banyumas sudah sesuai dengan aturan dan tata cara yang tertuang dalam peraturan daerah dan SK Bupati. Kelompok sasaran dalam kebijakan ini adalah masyarakat yang menjadi sasaran program pencegahan stunting. Organisasi pelaksana yaitu kelompok pelaksana, baik dari pemerintah yang tergabung dalam instansi terkait, kelompok masyarakat Puskesmas Terpadu, maupun pihak swasta yaitu rotary club. Faktor lingkungan yang dihadapi dalam pelaksanaan kebijakan pencegahan stunting berkaitan dengan faktor sosial dan ekonomi masyarakat. Kondisi gizi buruk yang menyebabkan stunting juga tidak terlepas dari kondisi sosial ekonomi masyarakat yang berpenghasilan rendah.Kata Kunci: Implementasi Kebijakan, Pencegahan Stunting